Corporate Social Responsibility and Creative Performance: The Indirect Effect of Creative Self-Efficacy, Spiritual Intelligence, and Organizational Identification - Sagheer, Omer; Muhammad Umer (UW Journal of Management Sciences, 2023)
Purpose: The relationship between CSR and improved attitudes and actions on the job is the subject of a growing corpus of study. Even while there is evidence that CSR boosts employee loyalty, motivation, contentment, and commitment, there is surprisingly little research on how CSR affects employees' ability to think creatively. Design and Methodology: The sample data were collected from Six Pakistani MNCs involved in CSR practices in the capital cities of Rawalpindi and Islamabad. These companies include Jazz, Telenor, Careem, Schlumberger, Berger Paints Pakistan, and McDonald's Pakistan. Only these six were chosen because they are the top-ranked organizations in Pakistan. The self-employed questionnaire was rotated via Google Forms. Out of 60 responses, 52 were considered for the present study. The repeated items, some questions left unchecked were excluded from the study. Findings: The results have shown that the Employee-managers who place a high priority on CSR campaigns and other practices are seen in the research to have positive effects on the firm, including increased employee dedication, loyalty, and innovation. Also, it was found that organizational identity mediates between creative self-efficacy and Spiritual Intelligence and has a positive effect on organizations’ performance. Implications: The findings provided useful insight for policymakers in MNCs organizations for planning and execution by incorporating CSR practices for the positive outcome and to maintain a positive environment in the organization for optimization of output. Keywords: Corporate Social Responsibility; Corporate Ability; Organizational Identification; Creative Self-Efficacy; Employee-Manager Relationship; Spiritual Intelligence; MNCs; Pakistan.